Sustained heavy drinking over 25 years is associated with increased N-terminal-pro-B-type natriuretic peptides in early old age: Population-based cohort study. (1st July 2020) - Britton, Annie; O'Neill, Dara; Kuh, Diana; Bell, Steven
Highlights: Prolonged heavy drinkers had higher levels of NT-proBNP, an important cardiac biomarker for heart failure, than moderate drinkers. This suggests a pathway through which prolonged heavy alcohol consumption may increase risk of this cardiovascular disease. Heavy drinkers could be screened for NT-proBNP levels to identify those at high risk earlier in the clinical stages of heart failure and targeted for risk reduction strategies. Abstract: Heavy alcohol consumption is associated with an increased risk of heart failure. We sought to investigate whether levels of NT-proBNP differ by alcohol consumption profiles, both current drinking as well as cumulative exposure to drinking over several decades in a general population sample. Methods: Data on 2054 participants (49% male) were taken from the UK Medical Research Council National Survey for Health and Development, a longitudinal cohort study based on a nationally representative sample of births in 1946. Categories of long-term alcohol consumption were created based on consumption over 25 years of observations and compared with levels of NT-proBNP measured at mean age 63. Results: We found that those who drank heavily (both currently and long-term) had higher levels of NT-proBNP than moderate drinkers, after adjusting for major confounders (age, sex, socio-economic position and smoking). As NT-proBNP has attracted attention as a biomarker for heart failure, this suggests a critical pathway through which heavy drinking may increase risk of this cardiovascular disease. When we looked at heavy drinkers who varied their intake over the decades, it was only the recently heavy group that had higher levels of NT-proBNP. Further work is needed to demonstrate whether effects are reversible upon cessation of heavy drinking, but this finding highlights the need to have repeated data to unpack dynamics over time. Conclusion: Our findings suggest heavy drinkers could be screened for NT-proBNP levels in order to identify those at high risk earlier in the clinical stages of heart failure and targeted for risk reduction strategies.